Office 2010 all-in-one for dummies - Weverka, Peter (For dummies, 2010)
Common tools you'll find in all Office applications ; Clear instructions for revising and collaborating on documents ; Tips on building tables, charts and diagrams in Excel, Word, and PowerPoint ; Word's tools for creating scholarly reports and white papers ; Advice on scheduling events with Outlook ; Secrets of PowerPoint presentations ; How to build an Access database from scratch ; Hints for creating newsletters in Publisher